Teacher Challenges in Adapting New Technology in Indonesian Language Learning: An Exploratory Study in Elementary School - Hamna; Muh. Khaerul Ummah BK; Mas’adi; Wahyudin P. Laubaha; Dewi Oktavia; Tiara Astian Ashar (Madako Elementary School, 2026)
This study was motivated by the challenges faced by teachers in adapting Indonesian language instruction to emerging technological platforms at the elementary school level. Such conditions have contributed to the suboptimal implementation of digital-based learning in classroom settings. The study employed a qualitative approach with an exploratory research design. Data were collected through in-depth interviews, participant observations, and document analysis to obtain a comprehensive understanding of teachers’ adaptation processes toward new educational technologies. The findings revealed five major challenges encountered by teachers in their efforts to adjust to technological advancements in the learning process of Grade V students at SDN 3 Nalu, particularly in the utilization of Artificial Intelligence (AI) and Interactive Flat Panel (IFP) smartboard technology. These findings indicate that teachers’ innovative capabilities and pedagogical flexibility play a strategic role in enhancing students’ participation and learning motivation. Despite encountering various obstacles, teachers demonstrated strong adaptive capacities through several initiatives. The implications of this study highlight the importance of strengthening teachers’ digital literacy, providing continuous professional development and training opportunities, and ensuring equitable access to technological infrastructure to support a more effective and sustainable transformation of educational practices.